The adenosine A2A receptor is a therapeutic target in neurological, heart and oncogenic diseases. (2nd September 2022) - Franco, Rafael; Lillo, Alejandro; Navarro, Gemma; Reyes-Resina, Irene
ABSTRACT: Introduction: Following approval of antagonists in Parkinson's disease therapy, the A2A adenosine receptor (A2A R) is gaining interest as a target to combat a variety of diseases. Areas covered: This review focuses on the therapeutic potential of targeting A2A R inside but also outside the central nervous system, more precisely to combat cardiac arrhythmias and to boost immune-based cancer therapies. The mechanism of regulation of the immune system by adenosine (Ado) is complex since several actors are involved, namely the enzymes that produce and degrade the compound and the four Ado receptors. Antagonists of A2A or andadenosine A2B Ado receptors lead to reduce their activation intracellular cAMP levels thus boosting immune responses. The literature search methodology consisted of reviewing the authors own collection of papers plus searches in the PubMed and Google Scholar databases from March 2021 to August 2022. Expert opinion: There is a pending issue, namely, how to demonstrate the neuroprotective potential of A2A R antagonists that would lead to delay neurodegenerative disease progression. In addition, A2A R antagonists and, eventually, dual A2A /A2B receptor antagonists have potential in the treatment of heart arrythmias and cancer. If adequate resources are allocated, it is a matter of time to confirm whether or not these possibilities become a reality.